PENDAMPINGAN MAHASISWA PROGRAM KAMPUS MENGAJAR ANGKATAN 7 DALAM UPAYA PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI DI SDN 3 REJOTANGAN KABUPATEN TULUNGAGUNG - Maskur Maskur; Aprilia Indi Prastika; Audrey Berlian Noormasari; Lina Gustaria Fillinanti Diah Saputri; Puput Ammalyah (Jurnal Pengabdian kepada Masyarakat, 2024)
The Campus Teaching Batch 7 program aims to improve students' literacy and numeracy skills through student mentoring at SDN 3 Rejotangan, Tulungagung Regency. This activity examines the effectiveness of the mentoring program in overcoming the problem of low student literacy and numeracy skills. The methods used are observation, interviews, and pre- and post-assistance tests to measure changes in students' abilities. The results show that there is a significant improvement in students' literacy and numeracy skills after receiving intensive assistance from students. This program also had a positive impact on students' learning motivation, as seen from the increased participation and enthusiasm of students in learning activities. The mentoring students acted as facilitators, providing interesting and relevant materials, and using interactive and fun learning methods. In addition, the collaboration between student assistants, teachers, and parents also supports the success of this program. Student assistance in the Teaching Campus Program Batch 7 is effective in improving students' literacy and numeracy skills at SDN 3 Rejotangan. Recommendations are given to develop similar programs in other schools to improve the quality of basic education in Indonesia.